ANALYSIS OF BASIC FACILITY NEEDS IN THE LAND AREA AT THE TANJUNG RU FERRY PORT, BANGKA BELITUNG PROVINCE - Vita Permata Sari; Febriansyah; Yulia Puspita Sari; Surnata; Novi Tri Susanto (AKSELERASI: Jurnal Ilmiah Nasional, 2026)
Tanjung Ru Ferry Port is essential as it is the only port that connects Bangka Island and Belitung Island via roll-on/roll-off ferry services. However, the condition of the onshore facilities at this port does not fully comply with the standards outlined in Minister of Transportation Decree No. 52 from 2004. Several major issues have been identified, including an inadequate waiting area, the absence of a gangway and weighbridge, and a lack of proper safety gear. This research aims to evaluate the state of onshore facilities and identify the unmet needs of these facilities. A descriptive quantitative method was employed, which included field observations, surveys, documentation, and an examination of applicable regulations. Findings reveal that most of the nine critical land facilities required are either absent or fail to meet the necessary standards.